2010
DOI: 10.1063/1.3368681
|View full text |Cite
|
Sign up to set email alerts
|

Detachment stabilization with n/m=1/1 resonant magnetic perturbation field applied to the stochastic magnetic boundary of the Large Helical Device

Abstract: It is found that the remnant island structure created by n/m=1/1 resonant magnetic perturbation field in the stochastic magnetic boundary of the Large Helical Device (LHD) [A. Komori et al., Nucl. Fusion 49, 104015 (2009).] has a stabilizing effect on formation of radiating plasma, realizing stably sustained divertor detachment operation with the core plasma being unaffected. The data from the several diagnostics, (profiles of electron temperature & density, radiation and temporal evolution of divertor particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 33 publications
6
69
0
Order By: Relevance
“…The island chains in helical SOLs provide a multi-null divertor configuration where the number, location and geometry of the X-points can be adjusted externally, thus having the potential of more flexible control of the radiation location for optimum power removal. Indeed, both W7-AS and LHD have demonstrated success in controlling and stabilizing the radiation layer outside the confinement region by externally manipulating the divertor geometry [54,55]. Numerically it is shown that the plasma-neutral interaction is not the main reason for the rollover of the recycling flux and downstream density in helical devices.…”
Section: Discussionmentioning
confidence: 99%
“…The island chains in helical SOLs provide a multi-null divertor configuration where the number, location and geometry of the X-points can be adjusted externally, thus having the potential of more flexible control of the radiation location for optimum power removal. Indeed, both W7-AS and LHD have demonstrated success in controlling and stabilizing the radiation layer outside the confinement region by externally manipulating the divertor geometry [54,55]. Numerically it is shown that the plasma-neutral interaction is not the main reason for the rollover of the recycling flux and downstream density in helical devices.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of a comparison between the EMC3/Eirene-based synthetic images and the IRVB images, data is taken from discharges in which an m/n = 1/1 magnetic island (where m and n are the indicies of the poloidal and toroidal harmonics, respectively) is used to break the m = 2, n = 10 symmetry of the LHD magnetic field and induce and stabilize a detached plasma [7][8][9]. In these discharges it has been observed that during the detachment with the magnetic island the radiation is localized in the x-point of the magnetic island which is toroidally localized and centered on the inboard side at the same field period as the o-point which is centered on the outboard side.…”
Section: Comparison Of Synthetic Images and Irvb Datamentioning
confidence: 99%
“…While the detached plasma is established in the LHD experiment, the radiation region exists at the stochastic region which is upstream from the divertor leg. In particular, in the case that the magnetic island is imposed, AXUVD and bolometer diagnostics have shown that the radiation region is localized around the X-point of the magnetic island [3,7]. This detachment in LHD can be thought to be a phenomenon similar to an X-MARFE in a tokamak [8], which can be sustained in the stochastic magnetic field at the X-point of the magnetic island.…”
Section: Detached Plasmasmentioning
confidence: 99%
“…In the previous study in LHD, the 1/3∼1/10 reduction of particle flux and heat load on the divertor plate has been observed by means of the divertor-probe measurement [3], which can be thought of as a detachment. While the detached plasma is established in the LHD experiment, the radiation region exists at the stochastic region which is upstream from the divertor leg.…”
Section: Detached Plasmasmentioning
confidence: 99%
See 1 more Smart Citation